Clinical Features, Management, and Molecular Characteristics of Familial Small Bowel Neuroendocrine Tumors - Lim, James Y.; Pommier, Rodney F. (Frontiers in Endocrinology, 2021)
Small bowel neuroendocrine tumors are rare tumors with an increasing incidence over the last several decades. Early detection remains challenging because patients commonly develop symptoms late in the disease course, often after the tumors have metastasized. Although these tumors were thought to arise from sporadic genetic mutations, large epidemiological studies strongly support genetic predisposition and increased risk of disease in affected families. Recent studies of familial small bowel neuroendocrine tumors have identified several novel genetic mutations. Screening for familial small bowel neuroendocrine tumors can lead to earlier diagnosis and improved patient outcomes. This review aims to summarize the current knowledge of molecular changes seen in familial small bowel neuroendocrine tumors, identify clinical features specific to familial disease, and provide strategies for screening and treatment.